2014
DOI: 10.1159/000362227
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Impairs Palatal Shelf Adhesion and Fusion in the <b><i>Tgf-β</i></b><sub>3</sub> Null Mutant

Abstract: The cleft palate presented by transforming growth factor-β3 (Tgf-β3) null mutant mice is caused by altered palatal shelf adhesion, cell proliferation, epithelial-to-mesenchymal transformation and cell death. The expression of epidermal growth factor (EGF), transforming growth factor-β1 (Tgf-β1) and muscle segment homeobox-1 (Msx-1) is modified in the palates of these knockout mice, and the cell proliferation defect is caused by the change in EGF expression. In this study, we aimed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…But the timing and location of TGFβ3 during palatogenesis suggests that TGFβ3 may contribute in MEE differentiation and periderm degeneration. Evidence also supports the role of IRF6 and ΔNp63 in MEE differentiation and maintenance through several pathways, including Wnt, Ephrin, TGFβ1, and Notch/Jag2 (Richardson et al, ; Lee et al, ; Murillo et al, ; Richardson et al, ; Risley et al, ; Moretti et al, ; Thomason et al, ; Yu et al, ; Ferretti et al, ; Iordanskaia and Nawshad, ; Fakhouri et al, ; Barrio et al, ; Kurosaka et al, ). During palatogenesis, the MEE cell surface is covered with a periderm layer, which prevents MEE cells from premature adhesion to other tissues within the oral cavity (Fitchett and Hay, ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…But the timing and location of TGFβ3 during palatogenesis suggests that TGFβ3 may contribute in MEE differentiation and periderm degeneration. Evidence also supports the role of IRF6 and ΔNp63 in MEE differentiation and maintenance through several pathways, including Wnt, Ephrin, TGFβ1, and Notch/Jag2 (Richardson et al, ; Lee et al, ; Murillo et al, ; Richardson et al, ; Risley et al, ; Moretti et al, ; Thomason et al, ; Yu et al, ; Ferretti et al, ; Iordanskaia and Nawshad, ; Fakhouri et al, ; Barrio et al, ; Kurosaka et al, ). During palatogenesis, the MEE cell surface is covered with a periderm layer, which prevents MEE cells from premature adhesion to other tissues within the oral cavity (Fitchett and Hay, ).…”
Section: Discussionmentioning
confidence: 85%
“…The question then remains, what regulates IRF6, if not TGFβ3? There are several candidates that are known to regulate IRF6, such as Wnt, Ephrin, TGFβ1, and Notch/Jag2 (Richardson et al, ; Lee et al, ; Murillo et al, ; Richardson et al, ; Risley et al, ; Yu et al, ; Iordanskaia and Nawshad, ; Barrio et al, ; Kurosaka et al, ). We have previously reported that TGFβ1 induces cell cycle arrest in the palatal epithelia by activating the CDK inhibitor, p15 ink4b (Iordanskaia and Nawshad, ); and TGFβ signaling via TGFβ receptor 2 regulates IRF6 and cell cycle arrest (Iwata et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In TGF␤3 KO mice, the expression of GARP in MEEs most likely ensures abundant TGF␤1 and TGF␤2 in this location. However, for reasons that are unclear, neither of these two molecules is able to compensate for the loss of TGF␤3 (28,29,37,38).…”
Section: Garp Is Essential For Mouse Palatogenesismentioning
confidence: 99%
“…At the current resolution in our study, the cell type of MES is consistent with cells in the oral cavity (Epi_Krt14), yet we can observe region-specific transforming signaling, Tgfβ3, and Pthlh, at MES. The Tgfβ3 signal has been reported to play an important role in the process of palatal adhesion and fusion (Barrio et al 2014; Hu et al 2015), while the Pthlh gene has been implicated in the epithelial–mesenchymal transition and cancer metastasis in previous studies (He et al 2018; Pitarresi et al 2021). For the first time, we observed the specific expression of Tgfβ3 and Pthlh signaling in the MES triangle, suggesting that they may mediate the epithelial–mesenchymal transition in the palatal fusion zone.…”
Section: Discussionmentioning
confidence: 99%